Personality traits in substance use disorders and obesity when compared to healthy controls. (29th April 2020) - Ramirez, Veronica; Wiers, Corinde E.; Wang, Gene‐Jack; Volkow, Nora D.
Abstract: Background and Aims: Although personality traits are implicated in substance use disorders (SUDs) and obesity, differences and similarities between them have not been assessed. Our main aim was to compare personality traits between people with different SUDs, obese people and healthy controls. Design: This was a secondary analysis of personality scores obtained from participants in neuroimaging studies from Brookhaven National Laboratory and the Laboratory of Neuroimaging, National Institutes of Health. Setting: United States. Participants/Cases: Individuals with obesity (OB) n  = 41, alcohol use disorder (AUD) n  = 39, marijuana use disorder (MUD) n  = 24, cocaine use disorder (CUD) n  = 100, and healthy controls (HC) n  = 117 (237 males and 84 females). Measurements: The Multidimensional Personality Questionnaire, which characterizes positive emotionality (PEM), negative emotionality (NEM) and constraint (CON) traits. Adjusted covariates included cigarette smoking status, age, gender and body mass index (BMI). Findings: Multivariate analysis of covariance showed a main group effect (i.e. OB, AUD, MUD, CUD and HC) only on NEM ( P <  0.0001, η 2  = 0.17) and CON ( P  = 0.005, η 2  = 0.12). Specifically, NEM was higher in AUD ( P  < 0.0001, d  = 10.4), CUD ( P  < 0.0001, d  = 8.2) and MUD ( P  = 0.001, d  = 9.2), but not in OB ( P  > 0.05, d  = 2.8) relative to HC. CUD showed lower CON ( P  = 0.015, d  = 5.4) and PEM ( P  = 0.018, d  = 4.8) than HC; however, these differences were not significant in the other groups. NEM and CON were negatively correlated for groups combined ( r  = −0.26, P  < 0.0001), and separately for OB ( r  = −0.49, P  = 0.001) and CUD ( r  = −0.22, P  = 0.03). Cigarette smoking status did not influence group differences in NEM, PEM or CON. Conclusions: Compared with healthy controls, people with substance use disorders appear to show higher negative emotionality, and people with cocaine use disorders appear to show lower positive emotionality and constraint traits. Similar findings were not found among people with obesity.